2019
DOI: 10.1128/jvi.00313-19
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Production Is Resistant to RNase L Antiviral Activity

Abstract: There is currently no knowledge of how the emerging human pathogen Zika virus (ZIKV) interacts with the antiviral endoribonuclease L (RNase L) pathway during infection. Since activation of RNase L during infection typically limits virus production dramatically, we used CRISPR-Cas9 gene editing technology to knockout (KO) targeted host genes involved in the RNase L pathway to evaluate the effects of RNase L on ZIKV infection in human A549 cells. RNase L was activated in response to ZIKV infection, which degrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 53 publications
(67 reference statements)
13
45
0
Order By: Relevance
“…We have previously shown that ZIKV activation of the OAS/RNase L pathway can be 127 detected by 24hpi (Whelan et al, 2019). Using host 28S and 18S rRNA degradation as a 128 measurement for RNase L activation, we show that RNase L activation during ZIKV 129 infection is mediated by the OAS3 isoform specifically (Figure 1A, left panel).…”
Section: Summary 25mentioning
confidence: 81%
See 3 more Smart Citations
“…We have previously shown that ZIKV activation of the OAS/RNase L pathway can be 127 detected by 24hpi (Whelan et al, 2019). Using host 28S and 18S rRNA degradation as a 128 measurement for RNase L activation, we show that RNase L activation during ZIKV 129 infection is mediated by the OAS3 isoform specifically (Figure 1A, left panel).…”
Section: Summary 25mentioning
confidence: 81%
“…No reuse allowed without permission. that OAS3 is the primary human OAS isoform required for 2-5A synthesis during viral 185 infections (Li et al, 2016, Whelan et al, 2019, and verified that other OAS isoforms did 186 not compensate for loss of OAS3 expression during ZIKV infections. Together these 187 results suggest that OAS3 is the primary producer of 2-5A during ZIKV infection, thereby 188 providing a useful system for investigating RNase L function independent of its catalytic 189 activity during viral infection.…”
Section: Effects Of Oas3 Knockout On Zikv Rf Function 174mentioning
confidence: 93%
See 2 more Smart Citations
“…We used an A549 cell line lacking ISG15, previously generated using CRISPR/Cas9 in our lab (Dos Santos et al, 2018). A549 cells were chosen due to their ability to support flavivirus replication and also to produce and respond to IFN-I (Gullberg et al, 2018;Wang et al, 2018;Whelan et al, 2019;Zhang et al, 2018).…”
Section: Isg15 Restricts DV and Zikv Replicationmentioning
confidence: 99%